Good Teacher Profile: Comparing Biobío’s Excellent Teachers’ Perspectives and Practices with the Ministry of Education Criteria - Mendoza Mardones, Ana; Sanzana Vallejos, Gloria; Pino, Pamela; Soto, José; Valdebenito, Laura (Journal of Interdisciplinary Perspectives, 2024)
This study aimed to compare the perceptions and practices of excellent teachers in a city in Chile and the Framework for Good Teaching (GTF) established by the Ministry of Education and Chilean teacher evaluation. The central objective was to compare the criteria for good teaching established by the Ministry of Education with the perceptions and practices of excellent teachers from a Chilean city, describing similarities and convergences. A qualitative descriptive methodology used a content analysis approach to describe teachers’ understanding supported by topic frequencies. Six criteria were selected as essentials for the Praxis: 1. Proficient in the national curriculum 2. Students’ characteristics 3. Students’ integral development; 4. Positive learning environment 5. Learning process evaluation, and 6. reflection on their practices. The findings showed several similarities, principally about the importance of curriculum management, preparing classes to plan, learning process evaluation, and integrating students’ interests. Further, it underscores the necessity to use different teaching strategies and technological resources to improve the learning process and as keys to educational success. At the same time, divergences address the need to consider integral students’ development, the learning environment, the teacher’s use of the school coexistence plan, collaborative reflection about the practice, and teachers’ commitment to the students beyond academics. Theoretical and practical implications highlight the necessity to consider teachers’ opinions, especially those who excel in their teaching practices, in creating prescribed ministerial frameworks. For teaching practices, teachers advocate for real collaboration time to improve their reflection and collaboration, positively impacting students learning.